Effect of gestational age and blood glucose on C‐peptide excretion rate and clearance in neonates. (30th July 2015) - Salis, Emma R; Soelbeck, Mikkel K; Reith, David M; Wheeler, Benjamin J; Broadbent, Roland S; Medlicott, Natalie J
Abstract : Aims: The aim of this study was to measure urinary C‐peptide concentrations, and then calculate C‐peptide clearance (Cl), and excretion rate (UER) in neonates. In addition, the effect of gestational age (GA) and blood glucose levels (BGL) on C‐peptide UER were investigated. Methods: Insulin concentrations in plasma and C‐peptide concentrations were measured in plasma and urine, in 20 neonates. Chemiluminescent immunoassays were used for insulin and C‐peptide measurements, with urine diluted to 40% with bovine serum albumin 1% in phosphate buffered saline. Urine volume and time of collection were recorded and used to calculate UER and Cl. Results: The mean Cl of C‐peptide was 0.309 ± 0.329 mL/min/kg, and UER was 0.0329 ± 0.0342 pmol/min/kg. Correlations between Cl or UER and GA were not significant ( P > 0.05). No significant correlation was shown between Cl or UER and BGL ( P > 0.05). Conclusions: Both Cl and UER were highly variable in neonates, but were not correlated with GA. Additionally, BGL did not appear to affect C‐peptide UER and Cl. As GA and BGL did not appear to affect Cl and UER, urinary C‐peptide may provide a non‐invasive method of measuring insulin production in neonates.